The Foreign Operations of Swedish Manufacturing Firms: Evidence from a Survey of Swedish Multinationals 1998 - Karolina Ekholm; Marie Hesselman (The Research Institute of Industrial Economics (IUI), 2000)
This paper presents the results of a survey of Swedish multinationals conducted in 1999. The survey was carried out in order to update an existing database on Swedish manufacturing firms with producing foreign affiliates collected by the Research Institute of Industrial Economics (IUI). The database covers information about the Swedish parts and the producing foreign affiliates of manufacturing firms with at least 50 employees. The first survey was conducted in the early 1970's and up until today, seven surveys have been conducted. The following years are covered: 1965, 1970, 1974, 1978, 1986, 1990, 1994 and 1998. The purpose of this paper is twofold. First, it serves as a documentation of the survey covering 1998. Second, we use the database to present descriptive evidence of trends in the activities of Swedish multinationals within the manufacturing sector.
Keywords: F21; F23; 330; Foreign Direct Investment; Multinational Firms; Foreign Affiliates; Multinationales Unternehmen; Industrie; Auslandsinvestition; Schwedisch; Ausländische Tochtergesellschaft; Welt